A Rare Case report on Rheumatic Origin of Severe Tricuspid stenosis (Med Phoenix, 2021)
Tricuspid stenosis is a very rare valvular disease due to narrowing of the orifice of the tricuspid valve of the heart. It is usually of rheumatic origin which is accompanied by other valvular lesions. Other causes of tricuspid stenosis include carcinoid syndrome, endocarditis, endomyocardial fibrosis, lupus erythematosus, right atrial myxoma, drug induced and congenital tricuspid atresia. Here we report a patient who had undergone percutaneous transluminal mitral commissurotomy (PTMC) followed by mitral restenosis with Severe Tricuspid Stenosis with Severe Tricuspid Regurgitation.